Performance and characteristics of digestive tract organs given Indigofera zollingeriana leaf meal and turmeric (Curcuma domestica) on Japanese quail. Issue 1 (April 2020) - Purwanti, S; Agustina, L; Siswoyo, A; Ahmadi, I
Abstract: Feed material that can be used as a substitute for soybean meal for quail livestock, one of which is Indigofera zollingeriana flour which has a crude protein content of 22-29% and turmeric added as natural antibiotics can increase quail performance. The aim of this study was to investigate the effects of Indigofera zollingeriana top leaf meal as substitution of soybean meal and turmeric added as a substitute for antibiotic on quail performance and the characteristics of the optimal digestive system. One hundred and sixty Japanese quail ( Coturnix-coturnix japonica ), at 7 weeks old were used in this study and kept in insulation cages. A randomized completely design was applied with four dietary treatments and five replications. Control diet, without Indigofera zollingeriana top leaf meal and turmeric meal (P0), Substitute 6% soybean meal protein with 10% Indigofera zollingeriana top leaf meal and 2, 5% turmeric meal (P1), Substitute 9% soybean meal protein with 15 % Indigofera zollingeriana top leaf meal and 2, 5% turmeric meal (P2), Substitute 12% soybean meal protein with 20 % Indigofera zollingeriana top leaf meal and 2, 5% turmeric meal. The ration used was isoprotein (20%) and isoenergy (2800 kcal kg-1). Variable observed were feed intake, body weight gain, feed conversion, carcass percentages and the length and weight of the digestive tract. The result of this study was no significant among treatments (P>0.05) for feed intake, feed conversion, carcass percentages and digestive tract organs. However, body weight gains significant increased (P<0.05) were P2 not deferent with P0, P1, and P3, but P1 and P3 different bigger than P0. The conclusion of this study was substitute soybean meal protein with Indigofera zollingeriana top leaf meal and turmeric meal can increased quail body weight gain.